Method for judging dispersing performance of coal water slurry additive in laboratory

The fluidity and stability of water coal slurry are detected by pressure-free static flow measurement and static water analysis method, and the problem of difficulty in accurately judging the performance of water coal slurry additives in the prior art is solved, and rapid and accurate detection and selection of high-quality additives are achieved.

CN119510704APending Publication Date: 2025-02-25HENAN BLACK ECOLOGICAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411522048.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively detect the fluidity and stability of water coal slurry, which leads to the inability to accurately judge the performance of water coal slurry additives.

Method used

The pressureless static flow degree measurement method was used to detect the flowability of water coal slurry, and the stability of water coal slurry was detected by the static water analysis method. The dispersion performance of water coal slurry additives was determined by combining the two.

Benefits of technology

It realizes rapid and accurate detection of the fluidity and stability of water and coal slurry, can effectively judge the performance of water and coal slurry additives, select cost-effective additives, and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510704A_ABST
    Figure CN119510704A_ABST
Patent Text Reader

Abstract

The invention belongs to a method for judging the dispersing performance of a coal water slurry additive in a laboratory. Comprising a coal water slurry fluidity detection method and a coal water slurry stability detection method, the coal water slurry fluidity detection method is a non-pressure static fluidity measurement method, and the coal water slurry stability detection method is a static water analysis method; the detection method is convenient and rapid, the used tool is simple, and the performance of the coal water slurry additive can be effectively judged, so that the coal water slurry additive with high cost performance is selected or coal slurry concentration is carried out, and the purposes of reducing cost and improving efficiency are achieved; the coal water slurry additive has the characteristic that the coal water slurry additive with good dispersing performance and high cost performance can be quickly developed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water-coal slurry detection, in particular to a method for judging the dispersion performance of water-coal slurry additives in a laboratory. Background Art

[0002] Coal-water slurry is composed of coal powder, water and a small amount of additives. Coal-water slurry can be pumped, atomized, stored and transported like oil, and can be used for gasification and combustion of various boilers. It is widely used in the fields of synthetic ammonia, coal-to-methanol, coal-to-gas, etc. Compared with the traditional use of coal, it shows a huge environmental protection and energy saving method. Coal-water slurry additives account for less than 1% of coal-water slurry, but they play a vital role. The performance of coal-water slurry additives directly affects the concentration, fluidity, stability and other indicators of the prepared coal slurry. According to relevant literature, most of the methods for judging the performance of coal-water slurry additives are imperfect. The national standard "Coal-Water Slurry Experimental Method" has clear standards for the detection of coal slurry concentration, apparent viscosity and stability, but does not mention the coal slurry fluidity index. However, relying solely on the apparent viscosity value cannot reflect the state of the coal slurry (thin or thick). Sometimes the apparent viscosity value of the test is high, the coal slurry state is thin; the apparent viscosity of the test is low, and the coal slurry is thick. The chemical industry standard "Industrial Naphthalenesulfonate Terpolymer Coal-Water Slurry Additive" only stipulates the technical indicators of the coal-water slurry additive itself, but does not stipulate the technical indicators of the tested coal-water slurry, and cannot reflect the differences in the preparation of coal slurries using coal-water slurry additives with different performance.

[0003] Based on this, how to detect the fluidity and stability of water-coal slurry has become an important link in the development of water-coal slurry additives. Summary of the invention

[0004] The purpose of the present invention is to provide a method for determining the dispersibility of coal water slurry additives in a laboratory to solve the problems raised in the above-mentioned background technology.

[0005] A method for judging the dispersibility of water-coal slurry additives in the laboratory, the method comprising a water-coal slurry fluidity detection method and a water-coal slurry stability detection method. The water-coal slurry fluidity detection method is a pressure-free static fluidity measurement method, and the water-coal slurry stability detection method is a static water analysis method.

[0006] The present invention overcomes the technical solution of judging the quality of water-coal slurry additives by measuring the viscosity of water-coal slurry in traditional technology. Specifically, the flowability of water-coal slurry is measured by a pressureless static fluidity measurement method, and the stability of water-coal slurry is judged by a static water analysis method; the quality of the performance of water-coal slurry additives is judged by the fluidity and stability of water-coal slurry.

[0007] The present invention provides a method for determining the dispersibility of a coal water slurry additive in a laboratory, wherein the coal water slurry fluidity detection method comprises the following steps:

[0008] Step 11: placing the first cylindrical mold on a flat plate;

[0009] Step 12: Pour the prepared water-coal slurry into the first cylindrical mold, and ensure that the water-coal slurry does not flow out through the bottom of the first cylindrical mold;

[0010] Step 13: slowly lift the first cylindrical mold to make the water-coal slurry in the first cylindrical mold fall onto the flat plate, and spread the water-coal slurry on the flat plate without vibration;

[0011] Step 14: Record the maximum diameter of the coal-water slurry spread on the flat plate. The larger the diameter, the better the fluidity of the coal-water slurry.

[0012] Preferably, the first cylindrical mold is a truncated cone structure with a large bottom and a small top, and both are open; the flat plate is made of acrylic material, and a plane rectangular coordinate system is provided on the upper surface of the flat plate, and the lower center position of the first cylindrical mold coincides with the point O position in the plane rectangular coordinate system.

[0013] Preferably, the first cylindrical mold is slowly lifted at a rate of 4 to 6 cm / s;

[0014] Preferably, the maximum diameter of the coal-water slurry is recorded after the coal-water slurry is spread on the flat plate for 60 seconds without vibration.

[0015] The present invention provides another method for determining the dispersibility of coal water slurry additives in a laboratory, wherein the coal water slurry fluidity detection method comprises the following steps:

[0016] Step 21: pouring the prepared water-coal slurry into a second cylindrical mold, the second cylindrical mold is a funnel-shaped structure, and a movable plug is provided at the bottom of the second cylindrical mold;

[0017] Step 22: When the second cylindrical mold is filled with water-coal slurry, the movable plug is opened and timing is performed;

[0018] Step 23: When the water-coal slurry has completely leaked out from the bottom of the second cylindrical mold, the timing is stopped. The shorter the time, the better the fluidity of the water-coal slurry.

[0019] The present invention also provides a method for determining the dispersibility of a water-coal slurry additive in a laboratory, wherein the water-coal slurry stability detection method comprises the following steps:

[0020] Step 31: pour the prepared water-coal slurry into a transparent static cylinder mold with an open top, and seal the top opening of the static cylinder mold with a plastic wrap;

[0021] Step 32: Let it stand for 24 hours in a vibration-free environment, and observe and record the stratification of water;

[0022] Step 33: Calculate the desorption rate by observing and recording the desorption stratification. The lower the desorption rate of the water-coal slurry is, the better the stability of the water-coal slurry is.

[0023] The present invention also provides a method for determining the dispersibility of a water-coal slurry additive in a laboratory. The preparation method of the prepared water-coal slurry is as follows:

[0024] Step 41: Use a crusher to crush the lump coal into coal powder with a size of 8 or larger, and mix the crushed coal powder evenly to ensure that the coal powder particle size distribution is uniform.

[0025] Step 42: Take a portion of the coal powder and put it into a vibrating screen to screen it into 8-40 mesh, 40-80 mesh, 80-200 mesh, 200-320 mesh, and different mesh sizes above 320 mesh for later use;

[0026] Step 43: using a laser particle size distribution instrument to detect the particle size distribution of the unscreened coal powder, and performing grading according to the requirements of different particle size distributions;

[0027] Step 44: accurately weigh the required coal powder and spare coal powder, additives and water according to different preparation requirements to prepare water-coal slurry.

[0028] According to the above technical scheme, a laboratory method for judging the dispersibility of water-coal slurry additives is provided. The present invention includes two specific technical schemes for detecting the fluidity of water-coal slurry. The above two technical schemes can be detected separately or jointly detected in a mutually verified manner. The present invention performs a water-coal slurry stability test after detecting the fluidity of water-coal slurry. The above detection method is convenient and fast, uses simple tools, and can effectively judge the performance of water-coal slurry additives, thereby selecting cost-effective water-coal slurry additives or carrying out coal slurry concentration to achieve the purpose of reducing costs and increasing efficiency. It has the characteristics of being helpful for the rapid development of water-coal slurry additives with good dispersibility and high cost-effectiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic structural diagram of the first cylindrical mold of the present invention.

[0030] Figure 2 It is a schematic structural diagram of the flat plate of the present invention.

[0031] Figure 3 It is a schematic structural diagram of the second cylindrical mold of the present invention.

[0032] Figure 4 It is a structural schematic diagram of the stationary cylinder mold of the present invention.

[0033] In the figure: 1. first cylindrical mold; 2. flat plate; 3. second cylindrical mold; 4. movable plug; 5. stationary cylindrical mold. DETAILED DESCRIPTION

[0034] The following is a further detailed description of the embodiments of the present invention in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0035] A method for judging the dispersibility of water-coal slurry additives in the laboratory, the method comprising a water-coal slurry fluidity detection method and a water-coal slurry stability detection method. The water-coal slurry fluidity detection method is a pressure-free static fluidity measurement method, and the water-coal slurry stability detection method is a static water analysis method.

[0036] A method for determining the dispersibility of a coal water slurry additive in a laboratory, the coal water slurry fluidity detection method comprising the following steps:

[0037] Step 11: placing the first cylindrical mold 1 on the flat plate 2;

[0038] Step 12: Pour the prepared water-coal slurry into the first mold cylindrical mold 1, and ensure that the water-coal slurry does not flow out through the bottom of the first mold cylindrical mold 1;

[0039] Step 13: slowly lift the first cylindrical mold 1, so that the water-coal slurry in the first cylindrical mold 1 falls entirely onto the flat plate 2, and spread the water-coal slurry on the flat plate 2 without vibration;

[0040] Step 14: Record the maximum diameter of the coal-water slurry spread on the flat plate 2. The larger the diameter, the better the fluidity of the coal-water slurry.

[0041] The first cylindrical mold 1 is a truncated cone structure with a large bottom and a small top, and both are open; the flat plate 2 is made of acrylic material, and a plane rectangular coordinate system is provided on the upper surface of the flat plate 2, and the lower center position of the first cylindrical mold 1 coincides with the point O position in the plane rectangular coordinate system.

[0042] The first cylindrical mold 1 is slowly lifted at a rate of 4 to 6 cm / s;

[0043] The maximum diameter of the water-coal slurry is recorded after the water-coal slurry is spread on the flat plate 2 for 60 seconds without vibration.

[0044] A method for determining the dispersibility of a coal water slurry additive in a laboratory, the coal water slurry fluidity detection method comprising the following steps:

[0045] Step 21: pour the prepared water-coal slurry into the second cylindrical mold 3, the second cylindrical mold 3 is a funnel-shaped structure, and a movable plug 4 is provided at the bottom of the second cylindrical mold 3;

[0046] Step 22: When the second cylindrical mold 3 is filled with water-coal slurry, the movable plug 4 is opened and timing is performed;

[0047] Step 23: When the water-coal slurry has completely leaked out from the bottom of the second cylindrical mold 3, the timing is stopped. The shorter the time, the better the fluidity of the water-coal slurry.

[0048] A method for determining the dispersibility of a coal water slurry additive in a laboratory, the coal water slurry stability detection method comprising the following steps:

[0049] Step 31: pour the prepared water-coal slurry into a transparent static cylinder mold 5 with an open top, and seal the top opening of the static cylinder mold 5 with a plastic wrap;

[0050] Step 32: Let it stand for 24 hours in a vibration-free environment, and observe and record the stratification of water;

[0051] Step 33: Calculate the desorption rate by observing and recording the desorption stratification. The lower the desorption rate of the water-coal slurry is, the better the stability of the water-coal slurry is.

[0052] A method for determining the dispersibility of coal water slurry additives in a laboratory, wherein the preparation method of the prepared coal water slurry is as follows:

[0053] Step 41: Use a crusher to crush the lump coal into coal powder with a size of 8 or larger, and mix the crushed coal powder evenly to ensure that the coal powder particle size distribution is uniform.

[0054] Step 42: Take a portion of the coal powder and put it into a vibrating screen to screen it into 8-40 mesh, 40-80 mesh, 80-200 mesh, 200-320 mesh, and different mesh sizes above 320 mesh for later use;

[0055] Step 43: using a laser particle size distribution instrument to detect the particle size distribution of the unscreened coal powder, and performing grading according to the requirements of different particle size distributions;

[0056] Step 44: accurately weigh the required coal powder and spare coal powder, additives and water according to different preparation requirements to prepare water-coal slurry.

[0057] The present invention is specifically a method for judging the dispersibility of water-coal slurry additives in the laboratory. It uses laboratory additive slurrying to detect the concentration, apparent viscosity value, fluidity, and stability index of the tested water-coal slurry to judge the performance of the water-coal slurry additive. Furthermore, the present invention provides a method and tool for judging the fluidity and stability of coal slurry. Compared with the known detection methods, it has the characteristics of simple operation and the ability to quantify the corresponding indicators, and can accurately and quickly judge the dispersibility of water-coal slurry additives; the present invention further supplements and improves the shortcomings of judging the fluidity of coal slurry only by viscosity value, and at the same time optimizes the method for judging the stability of coal slurry, which has practical application value and promotion significance. The present invention creatively combines two methods for judging the fluidity of coal slurry, and introduces stability for verification.

[0058] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0059] Example 1

[0060] A method for determining the dispersibility of coal water slurry additives in a laboratory, wherein the preparation method of the prepared coal water slurry is as follows:

[0061] Step 41: Use a crusher to crush the lump coal into coal powder with a size of 8 or larger, and mix the crushed coal powder evenly to ensure that the coal powder particle size distribution is uniform.

[0062] Step 42: Take a portion of the coal powder and put it into a vibrating screen to screen it into 8-40 mesh, 40-80 mesh, 80-200 mesh, 200-320 mesh, and different mesh sizes above 320 mesh for later use;

[0063] Step 43: using a laser particle size distribution instrument to detect the particle size distribution of the unscreened coal powder, and performing grading according to the requirements of different particle size distributions;

[0064] Step 44: accurately weigh the required coal powder and spare coal powder, additives and water according to different preparation requirements to prepare water-coal slurry.

[0065] According to the above preparation method, the water-coal slurry is prepared, and the prepared water-coal slurry is 500g, and the theoretical concentration is 63%; 331.58g of graded coal powder (coal powder solid content 95%), 168.42g of water, and 0.4725g of sodium lignin sulfonate additive (0.15% of dry basis coal mass);

[0066] The prepared water-coal slurry is used to test the concentration, viscosity, fluidity and stability indicators;

[0067] The concentration and viscosity of the coal water slurry are detected by traditional methods; the fluidity and stability indicators of the coal water slurry are detected by the coal water slurry fluidity detection method and the coal water slurry stability detection method of the present invention.

[0068] A method for determining the dispersibility of a coal water slurry additive in a laboratory, the coal water slurry fluidity detection method comprising the following steps:

[0069] Step 11: placing the first cylindrical mold 1 on the flat plate 2;

[0070] Step 12: Pour the prepared water-coal slurry into the first mold cylindrical mold 1, and ensure that the water-coal slurry does not flow out through the bottom of the first mold cylindrical mold 1;

[0071] Step 13: slowly lift the first cylindrical mold 1, so that the water-coal slurry in the first cylindrical mold 1 falls entirely onto the flat plate 2, and spread the water-coal slurry on the flat plate 2 without vibration;

[0072] Step 14: Record the maximum diameter of the coal-water slurry spread on the flat plate 2. The larger the diameter, the better the fluidity of the coal-water slurry.

[0073] The first cylindrical mold 1 is a truncated cone structure with a large bottom and a small top, and both are open; the flat plate 2 is made of acrylic material, and a plane rectangular coordinate system is provided on the upper surface of the flat plate 2, and the lower center position of the first cylindrical mold 1 coincides with the point O position in the plane rectangular coordinate system.

[0074] The first cylindrical mold 1 is slowly lifted at a rate of 4 to 6 cm / s;

[0075] The maximum diameter of the water-coal slurry is recorded after the water-coal slurry is spread on the flat plate 2 for 60 seconds without vibration.

[0076] A method for determining the dispersibility of a coal water slurry additive in a laboratory, the coal water slurry fluidity detection method comprising the following steps:

[0077] Step 21: pour the prepared water-coal slurry into the second cylindrical mold 3, the second cylindrical mold 3 is a funnel-shaped structure, and a movable plug 4 is provided at the bottom of the second cylindrical mold 3;

[0078] Step 22: When the second cylindrical mold 3 is filled with water-coal slurry, the movable plug 4 is opened and timing is performed;

[0079] Step 23: When the water-coal slurry has completely leaked out from the bottom of the second cylindrical mold 3, the timing is stopped. The shorter the time, the better the fluidity of the water-coal slurry.

[0080] A method for determining the dispersibility of a coal water slurry additive in a laboratory, the coal water slurry stability detection method comprising the following steps:

[0081] Step 31: pour the prepared water-coal slurry into a transparent static cylinder mold 5 with an open top, and seal the top opening of the static cylinder mold 5 with a plastic wrap;

[0082] Step 32: Let it stand for 24 hours in a vibration-free environment, and observe and record the stratification of water;

[0083] Step 33: Calculate the desorption rate by observing and recording the desorption stratification. The lower the desorption rate of the water-coal slurry is, the better the stability of the water-coal slurry is.

[0084] Example 2

[0085] A method for determining the dispersibility of coal water slurry additives in a laboratory, wherein the preparation method of the prepared coal water slurry is as follows:

[0086] Step 41: Use a crusher to crush the lump coal into coal powder with a size of 8 or larger, and mix the crushed coal powder evenly to ensure that the coal powder particle size distribution is uniform.

[0087] Step 42: Take a portion of the coal powder and put it into a vibrating screen to screen it into 8-40 mesh, 40-80 mesh, 80-200 mesh, 200-320 mesh, and different mesh sizes above 320 mesh for later use;

[0088] Step 43: using a laser particle size distribution instrument to detect the particle size distribution of the unscreened coal powder, and performing grading according to the requirements of different particle size distributions;

[0089] Step 44: accurately weigh the required coal powder and spare coal powder, additives and water according to different preparation requirements to prepare water-coal slurry.

[0090] According to the above preparation method, the water-coal slurry is prepared, and the prepared water-coal slurry is 500g, and the theoretical concentration is 63%; 331.58g of graded coal powder (coal powder solid content 95%), 168.42g of water, and 0.4725g of sodium humate additive (0.15% of dry basis coal mass);

[0091] The prepared water-coal slurry is used to test the concentration, viscosity, fluidity and stability indicators;

[0092] The concentration and viscosity of the coal water slurry are detected by traditional methods; the fluidity and stability indicators of the coal water slurry are detected by the coal water slurry fluidity detection method and the coal water slurry stability detection method of the present invention.

[0093] A method for determining the dispersibility of a coal water slurry additive in a laboratory, the coal water slurry fluidity detection method comprising the following steps:

[0094] Step 11: placing the first cylindrical mold 1 on the flat plate 2;

[0095] Step 12: Pour the prepared water-coal slurry into the first mold cylindrical mold 1, and ensure that the water-coal slurry does not flow out through the bottom of the first mold cylindrical mold 1;

[0096] Step 13: slowly lift the first cylindrical mold 1, so that the water-coal slurry in the first cylindrical mold 1 falls entirely onto the flat plate 2, and spread the water-coal slurry on the flat plate 2 without vibration;

[0097] Step 14: Record the maximum diameter of the water-coal slurry spread on the flat plate 2. The larger the diameter, the better the fluidity of the water-coal slurry. The first cylindrical mold 1 is a truncated cone structure with a large bottom and a small top, and both are open; the flat plate 2 is made of acrylic material, and a plane rectangular coordinate system is set on the upper surface of the flat plate 2. The lower center position of the first cylindrical mold 1 coincides with the position of point O in the plane rectangular coordinate system. The first cylindrical mold 1 is slowly lifted at a rate of 4 to 6 cm / s;

[0098] The maximum diameter of the water-coal slurry is recorded after the water-coal slurry is spread on the flat plate 2 for 60 seconds without vibration.

[0099] A method for determining the dispersibility of a coal water slurry additive in a laboratory, the coal water slurry fluidity detection method comprising the following steps:

[0100] Step 21: pour the prepared water-coal slurry into the second cylindrical mold 3, the second cylindrical mold 3 is a funnel-shaped structure, and a movable plug 4 is provided at the bottom of the second cylindrical mold 3;

[0101] Step 22: When the second cylindrical mold 3 is filled with water-coal slurry, the movable plug 4 is opened and timing is performed;

[0102] Step 23: When the water-coal slurry has completely leaked out from the bottom of the second cylindrical mold 3, the timing is stopped. The shorter the time, the better the fluidity of the water-coal slurry.

[0103] A method for determining the dispersibility of a coal water slurry additive in a laboratory, the coal water slurry stability detection method comprising the following steps:

[0104] Step 31: pour the prepared water-coal slurry into a transparent static cylinder mold 5 with an open top, and seal the top opening of the static cylinder mold 5 with a plastic wrap;

[0105] Step 32: Let it stand for 24 hours in a vibration-free environment, and observe and record the stratification of water;

[0106] Step 33: Calculate the desorption rate by observing and recording the desorption stratification. The lower the desorption rate of the water-coal slurry is, the better the stability of the water-coal slurry is.

[0107] Example 3

[0108] The preparation method of the water-coal slurry prepared in this embodiment, the method for detecting the fluidity of the water-coal slurry, the method for detecting the stability of the water-coal slurry, and the methods for detecting the concentration and viscosity of the water-coal slurry are all the same; the water-coal slurry is prepared according to the above preparation method, and the prepared water-coal slurry is 500g, and the theoretical concentration is 63%; 331.58g of graded coal powder (coal powder solid content 95%), 168.42g of water, and 0.4725g of sodium humate sample 1 additive (0.15% of the dry basis coal mass) are required.

[0109] Example 4

[0110] The preparation method of the water-coal slurry prepared in this embodiment, the method for detecting the fluidity of the water-coal slurry, the method for detecting the stability of the water-coal slurry, and the methods for detecting the concentration and viscosity of the water-coal slurry are all the same; the water-coal slurry is prepared according to the above preparation method, and the prepared water-coal slurry is 500g, and the theoretical concentration is 63%; 331.58g of graded coal powder (coal powder solid content 95%), 168.42g of water, and 0.4725g of sodium humate sample 2 additive (0.15% of the dry basis coal mass) are required.

[0111] Example 5

[0112] The preparation method of the water-coal slurry prepared in this embodiment, the method for detecting the fluidity of the water-coal slurry, the method for detecting the stability of the water-coal slurry, and the methods for detecting the concentration and viscosity of the water-coal slurry are all the same; the water-coal slurry is prepared according to the above preparation method, and the prepared water-coal slurry is 500g, with a theoretical concentration of 63%; 331.58g of graded coal powder (95% solid content of coal powder), 168.42g of water, and 0.4725g of aliphatic additive (0.15% of the dry basis coal mass) are required.

[0113] Example 6

[0114] The preparation method of the water-coal slurry prepared in this embodiment, the method for detecting the fluidity of the water-coal slurry, the method for detecting the stability of the water-coal slurry, and the methods for detecting the concentration and viscosity of the water-coal slurry are all the same; the water-coal slurry is prepared according to the above preparation method, and the prepared water-coal slurry is 500g, with a theoretical concentration of 63%; 331.58g of graded coal powder (95% solid content of coal powder), 168.42g of water, and 0.4725g of naphthalenesulfonate additive (0.15% of the dry basis coal mass) are required.

[0115] Test example

[0116] The test results of the above examples 1-5 are as follows:

[0117] Table 1 Viscosity values ​​of coal slurry prepared with different additives

[0118] name Preparation of coal slurry concentration Coal slurry viscosity (mPa·s) Sodium lignin sulfonate 63% 1083 Sodium Humate 63% 950 Sodium humate sample 1 63% 1000 Sodium humate sample 2 63% 1020 Fatty 63% 880 Naphthalenesulfonate 63% 800

[0119] Table 2 Fluidity and stability data of coal slurry prepared with different additives

[0120] Additive Name Preparation of coal slurry concentration Liquidity Method 1 Liquidity Method 2 24h water separation rate Sodium lignin sulfonate 63% 14.2cm 40s 2.50% Sodium Humate 63% 15.0cm 34s 3.10% Sodium humate sample 1 63% 16.7cm 28s 3.90% Sodium humate sample 2 63% 16.7cm 28s 3.50% Fatty 63% 17.5cm 22s 4.20% Naphthalenesulfonate 63% 18.6cm 15s 4.50%

[0121] The fluidity and stability of water-coal slurry present an opposite and contradictory relationship, that is, the better the fluidity, the more free water there is, and the easier it is for the water-coal slurry system to precipitate water. On the contrary, the worse the fluidity, the more fixed water is adsorbed on the surface of coal particles, the tighter the hydration film, and the more stable the slurry.

[0122] It can be seen from Table 1 that under the same coal slurry concentration, the lowest viscosity value data of naphthalene sulfonate is 800mPa·s, which can be judged that its viscosity reduction effect is the best, followed by aliphatic, sodium humate, sodium humate sample 1, sodium humate sample 2, and lignin sulfonate. It can be seen from Table 2 that the maximum expansion diameter of naphthalene sulfonate is 18.6cm, and the minimum flow time is 15s; the dispersion performance of other additives from best to worst is aliphatic, sodium humate sample 1 or 2, sodium humate, and sodium lignin sulfonate. Fluidity method 1 and fluidity method 2 verify each other, and it can be judged that its viscosity reduction effect is the best. At the same time, the water precipitation rate of naphthalene sulfonate is 4.50%, which is the highest, which also supports the results. Especially when the dispersion performance of the two additives is not much different, there will be deviations in judging the dispersion performance of the additives only from the viscosity value data. For example, the above two methods judge the difference in dispersion performance between sodium humate sample 1 or sample 2 and sodium humate. Since sodium humate is grafted with hydrophilic groups on the basis of sodium humate, its dispersibility for preparing coal slurry is better than that of ungrafted modified sodium humate. When the test values ​​of sodium humate sample 1 or sample 2 using fluidity method 1 or method 2 are the same, the lower the water separation rate value, the better the performance of its additive sample; for example, through analysis and detection, it is found that the degree of sulfonation of sodium humate sample 2 is higher than that of sodium humate sample 1. When the degree of sulfonation is high, there are more hydrophilic groups, so the water separation rate is lower, that is: sodium humate sample 2 is better than sodium humate sample 1. It can be seen from the above that the method of the present invention is more accurate; in summary, the present invention is a method for judging the dispersibility of water-coal slurry additives, which can improve and supplement the original detection method, and is simple and more accurate. Due to the differences in dispersibility between different types of additives and the differences in dispersibility between different products of the same type of additives, the specific embodiment results of the present invention are only responsible for this sample, but the invented method is universal.

[0123] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. A laboratory method for determining the dispersibility of coal water slurry additives, characterized in that: The method includes a method for detecting the fluidity of a water-coal slurry and a method for detecting the stability of a water-coal slurry. The method for testing the fluidity of water-coal slurry is the pressure-free static fluidity measurement method, and the method for testing the stability of water-coal slurry is the static water analysis method.

2. The method for determining the dispersibility of coal water slurry additives in a laboratory according to claim 1, characterized in that: The method for detecting the fluidity of coal water slurry comprises the following steps: Step 11: placing the first cylindrical mold (1) on the flat plate (2); Step 12: pouring the prepared water-coal slurry into the first mold cylindrical mold (1), and ensuring that the water-coal slurry does not flow out through the bottom of the first mold cylindrical mold (1); Step 13: slowly lift the first cylindrical mold (1) so that all the water-coal slurry in the first cylindrical mold (1) falls onto the flat plate (2), and spread the water-coal slurry on the flat plate (2) without vibration; Step 14: Record the maximum diameter of the coal-water slurry spread on the flat plate (2). The larger the diameter, the better the fluidity of the coal-water slurry.

3. The method for determining the dispersibility of coal water slurry additives in a laboratory according to claim 2, characterized in that: The first cylindrical mold (1) is a truncated cone structure with a large bottom and a small top, and both are open; the flat plate (2) is made of acrylic material, and a plane rectangular coordinate system is provided on the upper surface of the flat plate (2), and the lower center position of the first cylindrical mold (1) coincides with the position of point O in the plane rectangular coordinate system.

4. The method for determining the dispersibility of coal water slurry additives in a laboratory according to claim 2, characterized in that: The first cylindrical mold (1) is slowly lifted at a rate of 4 to 6 cm / s; 5. The method for determining the dispersibility of coal water slurry additives in a laboratory according to claim 2, characterized in that: The maximum diameter of the water-coal slurry is recorded after the water-coal slurry is spread on the flat plate (2) for 60 seconds without vibration.

6. A method for determining the dispersibility of coal water slurry additives in a laboratory according to claim 1, characterized in that: The method for detecting the fluidity of coal water slurry comprises the following steps: Step 21: pouring the prepared water-coal slurry into a second cylindrical mold (3), wherein the second cylindrical mold (3) is a funnel-shaped structure, and a movable plug (4) is provided at the bottom of the second cylindrical mold (3); Step 22: When the second cylindrical mold (3) is filled with the water-coal slurry, the movable plug (4) is opened and timing is performed; Step 23: When the water-coal slurry has completely leaked out from the bottom of the second cylindrical mold (3), the timing is stopped. The shorter the time, the better the fluidity of the water-coal slurry.

7. A method for determining the dispersibility of coal water slurry additives in a laboratory according to claim 1, characterized in that: The coal water slurry stability detection method comprises the following steps: Step 31: pour the prepared water-coal slurry into a transparent static cylinder mold (5) with an open top, and seal the top opening of the static cylinder mold (5) with a plastic wrap; Step 32: Let it stand for 24 hours in a vibration-free environment, and observe and record the stratification of water; Step 33: Calculate the desorption rate by observing and recording the desorption stratification. The lower the desorption rate of the water-coal slurry is, the better the stability of the water-coal slurry is.

8. A method for determining the dispersibility of coal water slurry additives in a laboratory according to any one of claims 1 to 7, characterized in that: The preparation method of the prepared coal water slurry is as follows: Step 41: Use a crusher to crush the lump coal into coal powder with a size of 8 or larger, and mix the crushed coal powder evenly to ensure that the coal powder particle size distribution is uniform. Step 42: Take a portion of the coal powder and put it into a vibrating screen to screen it into 8-40 mesh, 40-80 mesh, 80-200 mesh, 200-320 mesh, and different mesh sizes above 320 mesh for later use; Step 43: using a laser particle size distribution instrument to detect the particle size distribution of the unscreened coal powder, and performing grading according to the requirements of different particle size distributions; Step 44: accurately weigh the required coal powder and spare coal powder, additives and water according to different preparation requirements to prepare water-coal slurry.